2019
DOI: 10.3390/su11236588
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Relationship between Paradox Cognition, Green Industrial Production, and Corporate Performance

Abstract: Based on the theory of paradox cognition, a relationship model among paradox cognition, industrial green production, and enterprise performance has been constructed, which mainly focuses on a study on whether the paradox cognition can have positive influences on the green production behavior of industrial enterprises, and then further promote the improvement of enterprises' economic benefits. The author wrote this thesis on the basis of results obtained from 305 sample surveys and verified the direct and indir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
0
9
0
1
Order By: Relevance
“…GIC includes both intra-and extraorganizational green resources (Asiaei et al, 2022a;Xi et al, 2022), so orchestrating different dimensions of GIC can be a motivational element in environmental strategy. Paradox cognition is a kind of capability that enables firms to identify and balance symbolic and substantive environmental strategy, which provides a "both-and" mindset when developing environmental strategy (Gao and Khan, 2019;Pang et al, 2022).…”
Section: Configurational Frameworkmentioning
confidence: 99%
“…GIC includes both intra-and extraorganizational green resources (Asiaei et al, 2022a;Xi et al, 2022), so orchestrating different dimensions of GIC can be a motivational element in environmental strategy. Paradox cognition is a kind of capability that enables firms to identify and balance symbolic and substantive environmental strategy, which provides a "both-and" mindset when developing environmental strategy (Gao and Khan, 2019;Pang et al, 2022).…”
Section: Configurational Frameworkmentioning
confidence: 99%
“…Wei et al [31] found that enterprises with paradox cognition are more inclined to carry out effect change process and have a higher ability to cope with environmental uncertainty. Gao et al [32] found that paradox cognition has a significant positive impact on enterprises' green production behavior, and can also improve enterprises' financial performance by influencing "green product provision," "green production management," and "green production technology. "…”
Section: Mediating Variables: Paradox Cognition Smith Andmentioning
confidence: 99%
“…Companies have realised that green innovation is an essential factor for sustainable development and competitive advantage (Gao et al, 2019;Song & Yu, 2018). Researchers demonstrate that the green lifestyle dimension has become a structural and strategic element of successful organisations (Lončar et al, 2019).…”
Section: The Eco-friendly Frameworkmentioning
confidence: 99%